2011
DOI: 10.1088/0004-637x/734/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Simple Models of Metal-Line Absorption and Emission From Cool Gas Outflows

Abstract: We analyze the absorption and emission-line profiles produced by a set of simple, cool gas wind models motivated by galactic-scale outflow observations. We implement monte carlo radiative transfer techniques that track the propagation of scattered and fluorescent photons to generate 1D spectra and 2D spectral images. We focus on the Mg II λλ2796, 2803 doublet and Fe II UV1 multiplet at λ ≈ 2600Å, but the results are applicable to other transitions that trace outflows (e.g. Na I, H I Lyα, Si II). By design, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
317
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(355 citation statements)
references
References 71 publications
35
317
3
Order By: Relevance
“…The different degrees of blueshift for different lines were also suggested by Prochaska et al (2011) and were observed in the Keck spectra of SFGs by Erb et al (2012) and Kornei et al (2013) and in the VLT spectra by Tang et al (2014). Erb et al (2012, see also Kornei et al 2013) also found a variety of Mg II profiles in their individual spectra, and suggested some emission might originate from H II regions.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The different degrees of blueshift for different lines were also suggested by Prochaska et al (2011) and were observed in the Keck spectra of SFGs by Erb et al (2012) and Kornei et al (2013) and in the VLT spectra by Tang et al (2014). Erb et al (2012, see also Kornei et al 2013) also found a variety of Mg II profiles in their individual spectra, and suggested some emission might originate from H II regions.…”
Section: Discussionmentioning
confidence: 54%
“…For the eBOSS ELGs, the mean spectral resolution is about 2000 ~(60-70 km s 1 -) and the mean redshift precision is about 20 km s 1 -at redshift z ∼ 0.8. Our model is in principle similar to the one introduced by Scarlata & Panagia (2015, see also Rubin et al 2011Prochaska et al 2011), which the authors used as the basis in their radiative transfer simulations to interpret space-based observations in the FUV, though here we emphasize the statistical aspect of our model. Considering the sample size and S/N of our current data, we cannot yet place strong constraints on the model details, such as the functional form of the profiles or the parameters.…”
Section: Basics Of the Gas Outflow Modelmentioning
confidence: 93%
See 2 more Smart Citations
“…This can create a diffuse, low surface brightness emission component. Prochaska et al (2011) model the effect of reemitted light and conclude that in the extreme case that all of this light eventually escapes and is caught within the aperture, it can significantly reduce the observed equivalent width. We expect this effect to be very small in our analysis, however, since we are looking only at narrow slits and apertures that are small compared to the galaxies (1.5 arcsec corresponds to roughly 0.6 kpc in Haro 11 and just 0.3 kpc in ESO 338-IG04).…”
Section: Possible Stellar Contamination Of Na Dmentioning
confidence: 99%